Community Legal Awareness On Environmental Conservation in Irrigation Channels in Palleko Village, Polongbangkeng Utara District, Takalar Regency - Agus, Andi Aco; Nur, Ruslan Jabal; Zulfadli, Muhammad (Pinisi Business Administration Review, 2022)
This study aims to describe: (1) The legal knowledge of the people in Palleko Village on environmental conservation in irrigation canals, (2) Attitudes toward the legal behavior of the people in Palleko Village on environmental conservation in irrigation canals, (3) Efforts made by the Palleko Village Government in overcoming the problem of irrigation pollution. The number of respondents in this study was 30 people who lived in Palleko Village with random probability sampling, namely taking samples from the population randomly by taking into account the number of samples to generalize the sample to the population. The instruments used in this study were interview guide sheets and questionnaires. in the form of questionnaires, data collection procedures namely observation, interviews, and documentation. The data analysis used is to explain, describe, and describe according to the problem. Law Number 32 of 2009 concerning Environmental Protection and Management, (2) Based on the results of the questionnaire using the Likert scale, it shows that the attitude of the community's legal behavior towards environmental conservation is quite feasible with the percentage of 63.92%, (3) The efforts made by the Palleko Sub-District Government in overcoming the problem of environmental pollution are still not optimal, as evidenced by the lack of public facilities such as trash bins and government socialization that has not been evenly distributed to the public regarding the importance of environmental conservation.